Sustainability begins in the mind: from the user to the designer - Zakariya, Khalilah; Abdullah, Zakaria (2019)
Experiencing a place is as much about what we bring to the place, as it is about what the place has to offer. Collectively, our attitudes, awareness and actions towards a place can affect its sustainability. This session shares a personal experience of visiting camping sites, academic experience on ecotourism and observations of the changes and challenges faced by our society. As the act of achieving sustainability depends on the thought and actions of users, planners, designers, managers and the society at large, awareness, knowledge and commitment of all, directly and indirectly are of great importance in achieving the objective.